Odpowiedzi

2010-02-10T19:27:50+01:00
A) 6x-20-2=6x-22
b)2x+2-3x+1=-x+3
c)-3y+6+4y+8=y+14
d)5x-5y-5-4x-8=x-5y-13
e)6a+2b-2a+2b=4a+4b
f)2x-2-2x=-2
g)x²-x-6x+3x=x²-x
h)5a²-15a-3a²+15=2a²-15a+15
i:)3x²+y-xy+y=3x²+2y-xy
1 1 1
2010-02-10T19:29:47+01:00
A) 6(x-4)-2=6x-24-2=6x-26
b) 2(x+1)-3(x-1)=2x+2-3x+3=-1x+5
c) -3(y-2)+4(y+2)=-3y+6+4y+8=1y+14
d) 5(x-y-1)-4(x+2)=5x-5y-5-4x-8=1x-5y-13
e) 2(3a+b)-2(a-b)=6a+2b-2a+2b=4a+4b
f) 1\2(4x-4)-2x=2x-2-2x=-2
g) x(x-1)-3(x2-x)=x²-1x-3x²+3x=-2x²+2x
h) 5a(a-3)-3a(a-5)=5a²-15a-3a²+15a=2a²
i) 3x(x+1\3y)-2y(1\2x-1\2)=3x²+xy-xy+y=3x²+y



mam nadzieję ze pomogłam;))))))

aha i to rozwiązanie wyżej jest źle!!!!
1 5 1